SOSIALISASI DAN EDUKASI KEPADA ORANG TUA TENTANG ANAK AKTIF DAN HIPERAKTIF USIA DIBAWAH 12 TAHUN DI DESA SUKA NEGRI - Siti Nuraisyah (Bajang Institute, 2022)
Children under the age of 12 are the active period of a child and the time for these children to be free to move and be active. Time to be free to play and free to enjoy playing with their peers. Active children are children who are free to move, always move without obstacles from all things, especially in terms of their motor system. Children who are active even though they do a lot of movement, they are still able to focus on what they are doing. Hyperactive children are children who have activity beyond the active limits of normal children in general. Please note that hyperactive children are very difficult to focus attention, even controlling their body movements is very difficult. Children who are classified as hyperactive tend to be called children who have disorders and even require special treatment or therapy to deal with them. And also to distinguish active and hyperactive children, it is necessary to have several procedures, cannot directly diagnose a child into the hyperactive child group. The method in this scientific process is the process of socialization and education. Here the author provides some material about active and hyperactive children as well as education on how to handle them. Parents who have children in Suka Negri village are able to understand what an active child is and what its characteristics are, as well as how to handle and distinguish between an active child and a hyperactive child